PERANCANGAN SISTEM INFORMASI PENDATAAN PENDUDUK KELURAHAN SUNGAI JERING BERBASIS WEB DENGAN OBJECT ORIENTED PROGRAMMING - Febri Haswan (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2018)
The Sungai Jering Village Office is one of the agencies under the auspices of the Kuantan Singingi Regency government, in the processing of population data the Sungai Jering Village Head Office still uses conventional methods so that the work becomes less effective and efficient, with this system designed to facilitate the work of population data collection in managing population data more effectively and efficiently, this application can be used anywhere as long as it is connected to the internet network.